2020
DOI: 10.1177/1363461520938916
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of sub-Saharan children and adolescents: A scoping review

Abstract: The population of sub-Saharan children and adolescents is substantial and growing. Even though most of this population is vulnerable, there is no comprehensive understanding of the social-ecological factors that could be leveraged by mental health practitioners to support their resilience. The present study undertakes a narrative scoping review of empirical research (quantitative, qualitative, and mixed) on the resilience of children and adolescents living in sub-Saharan Africa to determine what enables their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 125 publications
(341 reference statements)
1
43
0
Order By: Relevance
“…Both the CD-RISC and RSA are commonly used resilience tools with strong psychometric properties (Salisu & Hashim, 2017; Windle et al, 2011), and these two tools were the most commonly used in the studies included in this review. Although some studies employed sociodemographic and/or contextual control variables, most of the tools used in the reviewed studies were primarily person-centered and non-socioecological, as noted and discussed elsewhere (Masten, 2014; Theron, 2020; Ungar, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Both the CD-RISC and RSA are commonly used resilience tools with strong psychometric properties (Salisu & Hashim, 2017; Windle et al, 2011), and these two tools were the most commonly used in the studies included in this review. Although some studies employed sociodemographic and/or contextual control variables, most of the tools used in the reviewed studies were primarily person-centered and non-socioecological, as noted and discussed elsewhere (Masten, 2014; Theron, 2020; Ungar, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Reviews of the studies accounting for the resilience of children and youth living in sub-Saharan Africa confirm the relevance of social-ecological explanations of resilience to African populations (Theron, 2020;Theron & Theron, 2010;Van Breda & Theron, 2018). Interestingly, these reviews found that personal and relational resources are the most prominently reported resources (compared to contextual or structural resources and cultural ones).…”
Section: A Social-ecological Approach To Human Resiliencementioning
confidence: 91%
“…Although multiple studies have documented the risks and resilience of youth living in sub-Saharan Africa (for systematic reviews of these studies, see Theron, 2020;Van Breda & Theron, 2018), few delimited the youth samples to emerging adults (i.e., worked exclusively with young people in the age range 18-29 or with samples with a mean age within that range). The exceptions include a handful of sub-Saharan studies that focused on emerging adult resilience in the face or aftermath of care-leaving (Frimpong-Manso, 2018;Van Breda & Dickens, 2017;Van Breda & Hlungwani, 2019), communicable disease (Harper et al, 2015), or armed conflict (Gustavsson et al, 2017), as well as studies that reported the resilience of residential university students challenged by structural disadvantage (Theron & Theron, 2013Van Breda, 2018;Zulu, 2019).…”
mentioning
confidence: 99%
“…Although this region continues to struggle with many issues that impact health, participants were confident in the will of the people and their capacity to withstand future stress and adversity. Personal and relational resources are the most prominently reported resources in accounting for the extraordinary resilience among sub-Saharan African communities (Theron, 2020), explained by one participant as, "they have a resilience that far exceeds anything you will see in the west" (Lead, Zam).…”
Section: Resilience and Capacity To Withstand Risksmentioning
confidence: 99%
“…Resilience, the capacity to develop or function successfully despite exposure to adversity (Masten, 2014), is strengthened by TSA's service inclusion: affirming choices the community makes, hearing their voice and integrating these with health-care services policies. Evaluation to improve existing programs and structure new ones, flexibility to change, response mobilization earlier rather than later and continuous learning through experience provide important resilience-enabling resources that are culturally situated (Theron, 2020). Thus, TSA's faith-based service inclusionthe inclusiveness of multiple actors, community-centric value (Reynoso et al, 2015) and embeddedness within the socio-cultural systemscan co-create opportunities for the dynamic processes of adaptation and adjustment to stress, risk and adversity that is central to resilience (Baker, 2009;Rutter, 2012).…”
Section: Resilience and Capacity To Withstand Risksmentioning
confidence: 99%